Interpreting Moral Values in the Short Story Dancing in Paradise by Agustrijanto - Julianita; Erni (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2025)
This research aims to interpret moral values related to responsibility, conscience, and obligations contained in the short story Dancing in Heaven by Agustrijanto. A qualitative approach is used to focus in-depth observation and analysis on the short story Dancing in Paradise by Agustrijanto. This research is based on the theory of Bertens (2004) with a qualitative descriptive research method with data in the form of quotes in short stories. The data collection technique uses the reading and recording technique (hermeneutics). The results of the study show that there are three moral values in the short story Dancing in Heaven by Agustrijanto, namely the first moral value related to responsibility consisting of hard work, never giving up, education, the second moral value of conscience consists of helping, sadness, sincerity, and the third moral value of obligation consists of worship and caring for others. From the analysis conducted by the researcher, it can be concluded that the short story Dancing in Heaven by Agustrijanto reveals that humans cannot be separated from the moral value of responsibility which is a fundamental aspect in social existence, it is difficult for humans to escape from the moral values of conscience and obligation because both are part of human personality that provide guidelines and behaviors that maintain order in life together. Through literary works such as the short story Dancing in Paradise it is able to prevent and filter the occurrence of moral crises in society which can then be implemented in all spheres of life both to families, leaders or fellow humans.